Biological Activity of Typical Irrigated Gray Soils - Abdukadirova Muxarram Arabboyevna (Central Asian Journal of Theoretical and Applied Science, 2022)
The article examines some physiological groups of microorganisms (ammonifiers, oligonitrophiles, fungi) in the typical irrigated gray soils of Orta Chirchik district of Tashkent region.